The Role of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) as a Government Institution Facilitating the Electronic Land Certificate Policy - Jennyola Savira; Gunawan Djajaputra (Journal of Law, Politic and Humanities, 2024)
The land sector is always seeing an increase in the community's demands. The state's land registration program and certificates of land rights are two measures that aim to provide community land-related activities more legal clarity. Technology has progressed to the point where traditional methods of registration and land rights certificates have given way to electronic alternatives. This change has led to a variety of responses and public concerns, one of which is whether the Indonesian state can realize this policy effectively in terms of regulations, institutions, infrastructure and society. This research was conducted to analyze the role of the ATR / BPN ministry as an institution that facilitates the electronic land certificate policy. The writing of this article uses normative research methods with a conceptual approach. The results of this study indicate that the ATR / BPN ministry has a crucial role in implementing this policy, starting from forming legal regulations, providing infrastructure, and creating innovations in the land sector to socialization in the community. The obstacles and constraints in implementing this policy include unprepared and optimized facilities and human resources, lack of public understanding, and imperfect legal regulations and security systems for electronic land certificates.